2018
DOI: 10.1049/iet-pel.2017.0278
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic boost converter based on stackable switching stages

Abstract: The authors propose a novel step-up converter with stackable switching stages that is suitable for renewable energy applications. On the one hand, the converter gain corresponds to that of the traditional quadratic boost converter, achieving an arbitrary exponential gain in extended configurations. On the other hand, the proposed converter requires a single switch, while the output voltage is partitioned among several capacitors. As argued in this work, the features of the proposed topology represent a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 31 publications
0
65
0
Order By: Relevance
“…The PV panel's I-V and P-V characteristics at different temperature conditions are shown in Figure 5a,b. From Figure 5a,b, it is observed that at static irradiation condition (1000 W/m 2 ), the MPP of the PV panel varies for each operating temperature (25,35,45, and 55 °C ) condition. The single-and double-diode circuit models' PV panel dynamic characteristics under different irradiation conditions (1000, 800, 600, and 400 W/m 2 ) are shown in Figure 4a,b.…”
Section: Mathematical Modeling Of Pv Panelmentioning
confidence: 99%
See 2 more Smart Citations
“…The PV panel's I-V and P-V characteristics at different temperature conditions are shown in Figure 5a,b. From Figure 5a,b, it is observed that at static irradiation condition (1000 W/m 2 ), the MPP of the PV panel varies for each operating temperature (25,35,45, and 55 °C ) condition. The single-and double-diode circuit models' PV panel dynamic characteristics under different irradiation conditions (1000, 800, 600, and 400 W/m 2 ) are shown in Figure 4a,b.…”
Section: Mathematical Modeling Of Pv Panelmentioning
confidence: 99%
“…From the literature survey [18][19][20][21][22][23][24][25][26][27], it is evident that there are different types of DC/DC converters used in standalone and grid-connected PV systems to control the load voltage. However, in this article, two high step-up DC-DC converters are discussed which are a SCBC and a SSBC at static and dynamic irradiation conditions and their performance results are compared with CBC.…”
Section: Analysis and Comparison Of Dc-dc Convertersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, various SSNINCITs have been presented in the literature. [15][16][17][18][19][20][21][22][23][24][25][26][27] Previous studies 15,18 are step-up converters with decreased BV on semiconductors that suffer from pulsating input (and output) current and large switch CS. The 16 is a conventional boost converter-based topology, in which the inductor has been replaced by an inductor-capacitor-diode cell, leading to quadratic voltage gain.…”
Section: Introductionmentioning
confidence: 99%
“…16 The converters presented in previous studies 17,20 are modular (extendable), with continuous input-current, low BV on switching devices and common-ground point between input and load. A previous study 17 has low switch CS, where another study 20 suffers from large switch CS, especially at extended versions. The topologies reported in previous studies 19,21 benefit from continuous input-current and low BV on semiconductors.…”
Section: Introductionmentioning
confidence: 99%